Post-Economic Liberalization Coping Strategies After Introduction of One Licence System in Tanzania: A Case of the Matengo Coffee Growers in Mbinga District - Mhando, David; Itani, Juichi (Tanzania Journal for Population studies and Development, 2008)
This paper examines coffee production in post-economic liberalisation in Mbinga District, Tanzania. It documents the coping strategies of the Matengo coffee growers after introduction of one licence in coffee marketing system in Tanzania in 2002. It gives a succinct history of coffee marketing as well as impact of the 2001 Coffee Industry Act. It explores how the coffee farmers sustained coffee production despite increasing costs of production and business malpractices of the Private Coffee Buyers (PCB). This paper is based on study conducted in Mbinga District. The sample size was 86 respondents who were selected randomly, as well as 20 members from two farmers groups. The study found out that production of high quality coffee, and proper timing of coffee marketing, are some of the strategies adopted by the Matengo coffee growers after introduction of one licensing system following the liberalization of coffee marketing system. The paper concludes that despite the odds of coffee cultivation after market liberalization, the Matengo coffee growers are used to the free market system, and have to a greater extent managed to adopt well the coping mechanisms to sustain coffee production.